Sejarah dan Fungsi Museum Palagan Perjuangan 1945 Bojongkokosan di Sukabumi - Ulfah Fauziah (Historia Madania: Jurnal Ilmu Sejarah, 2018)
This article is deals with the history and function of the 1945 Bojongkokosan Palagan Perjuangan Museum which was inaugurated in 1992, this museum aims to preserve historical heritages. This research uses historical research method with four steps, namely: Heuristics, that is, by collecting of written and spoken sources related to the Museum of the Battle of Struggle 1945, Bojongkokosan. Criticism by criticizing those sources that have been obtained. Interpretation, by interpreting the sources that have been obtained, and Historiography by writing the findings. It is found that, the 1945 Bojongkokosan Palagan Perjuangan Museum in Sukabumi has had a positive impact on the Sukabumi community. The 1945 Bojongkokosan Palagan Perjuangan Museum was founded in 1992 which began with the Bojongkokosan incident in Sukabumi. This museum serves as an appropriate tool for preserving historical heritage objects, as a means of education, a means of recreation, and a means of cultural attractions for the community. The museum has developed through times. This development is inseparable from the role of the management and the community who support progress in the museum. The aspects that has developed in the 1945 Bojongkoosan Palagan Perjuangan Museum include buildings, collections, and visitors.Kata Kunci : Museum, Heritage, Sukabumi